1994
DOI: 10.1007/bf00008338
|View full text |Cite
|
Sign up to set email alerts
|

Role of root derived organic acids in the mobilization of nutrients from the rhizosphere

Abstract: The role of organic acids in the mobilization of plant nutrients from the rhizosphere was assessed in seven contrasting soil types. The results indicated that malate was poor at mobilizing micronutrients from all the test soils, whilst citrate was capable of mobilizing significant quantities. Citrate was also capable of mobilizing P from one soil which possessed a large Ca-P fraction. This mobilization of P was due to both the complexing action of the citrate anion and due to the dissolution properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
374
2
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 627 publications
(386 citation statements)
references
References 27 publications
1
374
2
9
Order By: Relevance
“…However, it has been reported that there is wide genotypic variation in the utilization of sparingly soluble P among plant species and genotypes [26][27][28]. The results obtained in the present study show that genotype 102 was more P-efficient because it was able to produce up to 59% and 27% of its maximum dry weight when supplied with Al-P and Fe-P, respectively, whereas genotype 105 produced only 49% and 25%, respectively, of its maximum dry weight under the same conditions (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that there is wide genotypic variation in the utilization of sparingly soluble P among plant species and genotypes [26][27][28]. The results obtained in the present study show that genotype 102 was more P-efficient because it was able to produce up to 59% and 27% of its maximum dry weight when supplied with Al-P and Fe-P, respectively, whereas genotype 105 produced only 49% and 25%, respectively, of its maximum dry weight under the same conditions (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for exudates efficiency, roots have to limit the size of rhizosphere community. Jones and Darrah (1994) explained that plants have several mechanisms in reducing soil community magnitude in their root zones. Primarily, plants decline their root exudates productivity.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time organic acids may derive from organic matter (root or shoot residues) decomposition, promoted by microorganisms (PII et al, 2015). The dissolved organic compounds in the soil solution have a high affinity with heavy metals, reducing the potential toxicity for plants (JONES;DARRAH, 1994;MEIER et al, 2012;PÉREZ-ESTEBAN et al, 2014).…”
Section: Agronomic Practices To Reduce the Toxicity Of Heavy Metals Imentioning
confidence: 99%